2016
DOI: 10.1097/wnr.0000000000000487
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic antidepressants decrease hedonic signals but leave learning signals in the nucleus accumbens unaffected

Abstract: Investigating the effects of serotonergic antidepressants on neural correlates of visual erotic stimulation revealed decreased reactivity within the dopaminergic reward network along with decreased subjective sexual functioning compared with placebo. However, a global dampening of the reward system under serotonergic drugs is not intuitive considering clinical observations of their beneficial effects in the treatment of depression. Particularly, learning signals as coded in prediction error processing within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…Though, in this study, attenuated neural activations under REB were also found within the medial orbitofrontal cortex, previously related to the coding of pleasantness or received reward ( 37 ). Evidence supporting the interpretation of a differential modulation of primary erotic and secondary monetary rewards within the Nacc ( 11 ) highly similar to the current study was also found in our previous study with the SSRI paroxetine. The similarity of the findings under the noradrenergic agent REB as found in this study may be plausible considering some anatomical overlap of these two neuromodulatory pathways ( 21 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Though, in this study, attenuated neural activations under REB were also found within the medial orbitofrontal cortex, previously related to the coding of pleasantness or received reward ( 37 ). Evidence supporting the interpretation of a differential modulation of primary erotic and secondary monetary rewards within the Nacc ( 11 ) highly similar to the current study was also found in our previous study with the SSRI paroxetine. The similarity of the findings under the noradrenergic agent REB as found in this study may be plausible considering some anatomical overlap of these two neuromodulatory pathways ( 21 ).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, we now examined neural correlates of secondary reward and prediction error processing under reboxetine and amisulpride compared to placebo within the same healthy study sample in which we recently investigated the hedonic aspects of primary rewards by visual erotic picture stimulation ( 14 ). Paralleling our previous investigations on serotonergic agents ( 11 ), we focused on the Nacc as core region of the mesolimbic dopaminergic system ( 4 , 5 ) and expected unimpaired neural prediction error signals under the noradrenergic antidepressant reboxetine. The hypothesis was guided by findings of some anatomical overlap of the serotonergic and noradrenergic system ( 21 ) and the clinical observation that successful outcomes in environments requiring learning and adaptation of behavior such as behavioral psychotherapy, are even facilitated by antidepressants ( 22 ).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Regarding reward processing, whether SSRI treatment influences functional activity during reward tasks in patients with depression remains unclear. In healthy controls, SSRI treatment was shown to reduce the responsiveness to reward in fMRI (Macoveanu et al, 2014;Graf et al, 2016). However, Stoy et al (2012) evidenced a hyporeactivity to reward in unmedicated depressed patients, which is normalized after successful SSRI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Darüber hinaus wird das dopaminerge Belohnungssystem durch weitere Neuromodulatoren beeinflusst. So konnten wir in unserer Abteilung die Beeinflussung des dopaminergen Belohnungssystems durch das Serotonin-und Noradrenalinsystem mittels funktioneller Magnetresonanztomografie (fMRT) bildgebend darstellen (12)(13)(14)(15)(16)(17). In diesem Artikel sollen grundlegende Mechanismen und klinische Aspekte zur Beeinflussung des dopaminergen Belohnungssystems durch das Opioidsystem vorgestellt werden.…”
Section: Discussionunclassified